TRANSFORMATION OF PHRASEOLOGICAL UNITS IN THE RUSSIAN LANGUAGE IN THE 21ST CENTURY (Scientific journal of the Fergana State University, 2025)
The article is devoted to the changes in Russian phraseology in the 21st century under the influence of sociocultural and technological transformations. The analysis revealed the loss of relevance of some traditional phraseological units, the adaptation of others to new conditions, and the emergence of new ones related to digitalization. The study emphasizes the importance of phraseology as indicators of cultural changes and mechanisms of linguistic adaptation.